CORPORATE SOCIAL RESPONSIBILITY, INTELLECTUAL CAPITAL, AND FIRM VALUE: A CASE STUDY OF ENERGY COMPANIES IN INDONESIA - Wicaksono, Ignatius Geraldo; Eko Rizkianto (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2025)
This study aims to analyse the relationship between the independent variable Corporate Social Responsibility (CSR), the mediating variable Intellectual Capital measured through the Variable Added Intellectual Coefficient (VAIC), which includes Human Capital Efficiency (HCE), Structural Capital Efficiency (SCE), and Capital Employed Efficiency (CCE), and the dependent variable firm value represented by Tobin’s Q. Additionally, control variables such as firm size, leverage, and sustainability reporting are included in the analysis. Data for this study were obtained from companies listed in the IDX Energy sector index during the period 2018-2022. Based on the research findings, a significant relationship was found between Corporate Social Responsibility (CSR) and Tobin’s Q, indicating that CSR practices contribute to firm value as measured by Tobin’s Q. The mediating variable, Intellectual Capital, also has a significant impact on Tobin’s Q. The results of the mediation model analysis indicate that intellectual capital plays a role as an intermediary in the relationship between CSR and Tobin’s Q.